Distribution pattern and pathologic analysis of metastatic sentinel and non-sentinel lymph nodes in lymphatic basin dissection for clinical T2/T3 oral cancer with clinical N0 status. Issue 4 (August 2022) - Hirakawa, Hitoshi; Matsuzuka, Takashi; Uemura, Hirokazu; Yoshimoto, Seiichi; Miura, Kouki; Shiotani, Akihiro; Sugasawa, Masashi; Homma, Akihiro; Yokoyama, Junkichi; Tsukahara, Kiyoaki; Yoshizaki, Tomokazu; Hanai, Nobuhiro; et al.
Abstract: Objective: The localization pattern of metastatic sentinel lymph node (SN) and non-SNs and pathologic analysis of metastatic lymph nodes in SN lymphatic basin dissection (SLBD) were investigated in patients with cT2/T3cN0 oral squamous cell carcinoma (OSCC). Methods: This prospective multicenter trial involved 10 institutions nationwide in Japan. A total of 57 patients were enrolled. The lateral neck was divided into 5 lymphatic basins. The lymphatic basin containing SNs was defined as the SN lymphatic basin. All patients underwent SLBD with backup selective neck dissection (I-III) combined with primary tumor removal. When SNs were found outside of levels I-III, including in the contralateral neck, SLBD was performed by removing the compartments containing SNs separately. SN metastasis was classified as isolated tumor cells (ITCs), micrometastasis, or macrometastasis. ITCs are defined as a lesion no larger than 0.2 mm in largest dimension and are classified as pN0. Results: SN metastasis was observed in 22 cases. All metastatic lymph nodes, including false-negative cases, were detected in the SN lymphatic basin. Isolated tumor cells in the SNs did not affect prognosis, whereas micrometastasis tended to have poor prognosis. After adjusting for other risk factors, a positive SN remained a significant predictor of poor 5-year overall survival in pT2-4 OSCC. Conclusion: SLBD for intraoperative SN biopsy is a sufficient therapeutic procedure and is valuable for determining pathologic nodal stage in OSCC. SN positivity was demonstrated to be an independent predictor of poor prognosis in patients with pT2-4 disease undergoing SLBD with backup selective neck dissection (I-III).